Bacterial production of the fungus‐derived cholesterol‐lowering agent mevinolin. (29th January 2014) - Bose, Utpal; Hodson, Mark P.; Shaw, P. Nicholas; Fuerst, John A.; Hewavitharana, Amitha K.
ABSTRACT Forty‐five strains from two different species (Salinispora arenicola and Salinispora pacifica) were isolated from three different marine sponge species in the Great Barrier Reef region of Australia. We found that two of the strains of Salinispora arenicola (MV0335 and MV0029) produced mevinolin, a fungus‐derived cholesterol‐lowering agent. Compound structure was determined using an integrated approach: (a) high performance liquid chromatography‐quadrupole time‐of‐flight‐mass spectrometric analysis with multimode ionization (electrospray ionization and atmospheric pressure chemical ionization) and fast polarity switching; and (b) database searching and matching of monoisotopic masses, retention times and mass spectra of the precursor and product ions of the compounds of interest and the authentic reference standards thereof. Copyright © 2014 John Wiley & Sons, Ltd.